2009
DOI: 10.1099/mic.0.025890-0
|View full text |Cite
|
Sign up to set email alerts
|

Population heterogeneity in Methylobacterium extorquens AM1

Abstract: Heterogeneity of cells within exponentially growing populations was addressed in a bacterium, the facultative methylotroph Methylobacterium extorquens AM1. A transcriptional fusion between a well-characterized methanol-inducible promoter (P mxaF ) and gfp uv was used with flow cytometry to analyse the distribution of gene expression in populations grown on either succinate or methanol, correlated with forward scatter as a measure of cell size. These cell populations were found to consist of three major subpopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…This result is interesting in the light of a series of recent studies reporting phenotypic variation between genetically identical bacteria that live in homogeneous environments (4,9,10,22,24,(26)(27)(28). These differences include cell size, interdivision intervals, gene expression, and behavior.…”
Section: Vol 193 2011 Pole Age Affects M Extorquens Cell Size and mentioning
confidence: 79%
See 1 more Smart Citation
“…This result is interesting in the light of a series of recent studies reporting phenotypic variation between genetically identical bacteria that live in homogeneous environments (4,9,10,22,24,(26)(27)(28). These differences include cell size, interdivision intervals, gene expression, and behavior.…”
Section: Vol 193 2011 Pole Age Affects M Extorquens Cell Size and mentioning
confidence: 79%
“…extorquens is a facultative methylotroph that is ubiquitous in aquatic and terrestrial environments (15) and is often associated with plants (8). M. extorquens strain AM1 is a genetic model system (31) that shows substantial variation in cell size and interdivision intervals (26,27) between genetically identical cells. Motivated by these reports on phenotypic variation, we asked three questions about cell size asymmetry and the timing of cell division.…”
mentioning
confidence: 99%
“…Cells were washed once with the corresponding medium without Tet and were resuspended in the same medium at an OD 600 of approximately 0.4 to 0.5. Fluorescence measurements were carried out with a Shimadzu RF-5301PC fluorimeter as described previously (42). Green fluorescent protein (GFP) UV excitation was conducted at 405 nm, and emissions were monitored at 509 nm.…”
mentioning
confidence: 99%
“…The 352-bp fragment containing the ectR1-ectA intergenic region was amplified by PCR (the primers are shown in Table S2) and cloned into the pCR2.1 vector. The fragments were subsequently excised by PstI and BamHI and then cloned into the pTSGex promoter probe vector (42), resulting in a construct (pEBP1) containing the respective DNA fragments upstream of the promoterless reporter gene gfp. The resulting constructs were transformed into E. coli S17-1 (39) and then transferred into M. alcaliphilum 20Z and the EBPR01 mutant via conjugation using plasmid pRK2073 as a helper (11).…”
mentioning
confidence: 99%
“…Recently, a surge of evidences found that isogenic populations of microorganisms show substantial cell-to-cell heterogeneity at both cellular and molecular levels (Becskei et al, 2005;Colman-Lerner et al, 2005;Golding et al, 2005;Kelly & Rahn, 1932;Kuang et al, 2004;Le et al, 2005;Lidstrom & Meldrum, 2003;Maloney & Rotman, 1973;Pedraza & van Oudenaarden, 2005;Rosenfeld et al, 2005;Siegele & Hu, 1997;Strovas & Lidstrom, 2009;Strovas et al, 2007). The mechanisms that contribute to this gene expression heterogeneity include intrinsic heterogeneity that exists in biology, noise in the transcription machinery, micro-scale chemical gradients, and genotypic variations because of mutations and selection in individual cells (Stewart & Franklin, 2008).…”
Section: Introductionmentioning
confidence: 97%